The role of dual-energy X-ray absorptiometry in the detection of secondary skeletal involvement in a female patient with Gardner syndrome and HIV infection - Sytor, Maksym; Nechaiev, Mykyta; Balatska , Nataliya; Kozlova, Oksana; Ruzhylo, Kateryna (The Ukrainian Scientific Medical Youth Journal, 2026)
gardner syndrome is a rare genetic disorder, considered a phenotypic variant of familial adenomatous polyposis, which is associated with an aberration in the adenomatous polyposis coli (APC) gene. It is characterized by a combination of intestinal (colonic polyps) and a wide spectrum of extracolonic manifestations, including osteomas, desmoid tumors, epidermal cysts, hypertrophy of the retinal pigment epithelium, follicular thyroid cancer, and others. This article describes a clinical case of atypical bone changes in a female patient with Gardner syndrome, HIV infection, chronic post-hemorrhagic anemia, and hypothyroidism in a state of medical compensation. Gardner syndrome was confirmed at the age of three by endoscopic and morphological examination of multiple adenomatous polyps in the esophagus, stomach, duodenum, and colon. HIV infection was diagnosed at the age of 13.5 years, for which the girl receives antiretroviral therapy (ART). At the age of 17, she was referred for dual-energy X-ray absorptiometry (DXA), which revealed areas of localized increased bone mineral density in the projection of the upper third of the skull bilaterally. Subsequent skull radiography in the anteroposterior projection identified these changes as pronounced bilateral hyperostosis, while magnetic resonance imaging (MRI) of the brain further visualized diffuse thickening of the skull bones, emphasized at the vault level, with no pathological changes in the brain parenchyma. Thus, the detected hyperostosis had no clear clinical manifestations but became an incidental diagnostic finding during a routine dual-energy X-ray absorptiometry scan. The described case also illustrates the need for a multidisciplinary approach to managing patients with comorbid pathologies, as only the collaboration of doctors from different specialties allows for the correct interpretation of the results and determination of the optimal tactics for further examination and treatment. The detected hyperostosis in an adolescent with HIV infection and Gardner syndrome may likely be attributed to severe chronic anemia, which may have both diagnostic and prognostic significance. This case highlights the potential utility of X-ray absorptiometry that can serve not only as a method for quantitative assessment of bone mineral density but also as an additional tool for detecting skeletal structural changes that require further verification using other diagnostic imaging methods.